DEVELOPMENT OF MOBILE DEVICE FOR GAMMA RADIATION MEASUREMENT UTILIZING LORA AS THE COMMUNICATION MEANS - I Putu Susila; Agung Alfiansyah; Istofa Istofa; Sukandar Sukandar; Budi Santoso; Suratman Suratman (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2019)
Public protection is one of important issues when operating nuclear facility. In case of accident occurs, the facility owner and related organizations shall make decision whether to evacuate people or not, based on the level of the accident and radiation dose rate released to the environment. In this study, as part of the decision support system for nuclear emergency response, a prototype of mobile radiation measurement system has been developed. The device consists of Geiger-Muller (GM)-based radiation measurement board, Global Positioning System (GPS) module, microcontroller board, and low power LoRa module for communication. Radiation dose rate along with its geoposition were recorded and sent to base station equipped with LoRa gateway for connecting LoRa network to TCP/IP-based network. The measurement data is then published to storage server using Message Queuing Telemetry Transport (MQTT) protocol. Power consumption, measurement of counter/timer accuracy, communication ranges testing, and radiation dose rate measurement were performed around Puspiptek area to demonstrate the functionality of the system.Keywords: Radiation monitoring, Decision Support System, Mobile, LoRa, GPS